2021
DOI: 10.3390/ijms222111989
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Alternative Splicing and Non-Coding RNAs Reveal Complicated Transcriptional Regulation in Cannabis sativa L.

Abstract: It is of significance to mine the structural genes related to the biosynthetic pathway of fatty acid (FA) and cellulose as well as explore the regulatory mechanism of alternative splicing (AS), microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the biosynthesis of cannabinoids, FA and cellulose, which would enhance the knowledge of gene expression and regulation at post-transcriptional level in Cannabis sativa L. In this study, transcriptome, small RNA and degradome libraries of hemp ‘Yunma No.1’ were es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 114 publications
2
9
0
Order By: Relevance
“…We indeed find evidence for differential splicing of CsPT1 and multiple other CBGAS-related genes (Figure S1) between a high THC variety (White Cookies) and a high CBD variety (Canna Tsu), but with a small magnitude of difference as well as sample size, and therefore should be confirmed by additional studies. However, in support of our findings, a recent study reported alternative splicing events at the CBGAS locus, as well as others in the cannabinoid biosynthesis pathway, though tests for differential splicing between varieties were not performed (Wu et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…We indeed find evidence for differential splicing of CsPT1 and multiple other CBGAS-related genes (Figure S1) between a high THC variety (White Cookies) and a high CBD variety (Canna Tsu), but with a small magnitude of difference as well as sample size, and therefore should be confirmed by additional studies. However, in support of our findings, a recent study reported alternative splicing events at the CBGAS locus, as well as others in the cannabinoid biosynthesis pathway, though tests for differential splicing between varieties were not performed (Wu et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 3 male red deer were selected to collect antler samples at about 30 d, 60 d and 90 d growth stages, so that there were 3 samples from different individuals at each time point. In high-throughput sequencing, every sample pool was a mix of equal amount of RNAs from three individual male deer, as was the case in other studies [ 7 , 40 , 41 , 42 ], which indicated that this method was acceptable. However, studies with at least biological replicates may be more meaningful and acceptable compared with RNA pools, though each pool is collected with at least three samples.…”
Section: Discussionmentioning
confidence: 92%
“…To decipher the regulation of miRNAs in NATs and STs in C. sativa, we downloaded all the released plant mature miRNA sequences (V 22.1) from miRbase (Kozomara et al, 2019). Then we collected the published miRNA sequences of C. sativa from our previous report (Wu et al, 2021). Then, these miRNAs' targeted NATs and STs were predicted using the psRNATarget server with a penalty score of ≤ 2.5 (Dai et al, 2018).…”
Section: Prediction Of Mirna Targetsmentioning
confidence: 99%